2022
DOI: 10.3389/fpubh.2022.904279
|View full text |Cite
|
Sign up to set email alerts
|

Disease Characteristics, Care-Seeking Behavior, and Outcomes Associated With the Use of AYUSH-64 in COVID-19 Patients in Home Isolation in India: A Community-Based Cross-Sectional Analysis

Abstract: BackgroundDuring the second wave of the COVID-19 pandemic in India, the Ministry of Ayush conducted a community study to provide therapeutic care to patients with asymptomatic, mild, and moderate COVID-19 in home isolation based on the empirical evidence generated on the efficacy of AYUSH-64 in COVID-19.ObjectiveTo document disease characteristics, care-seeking behavior, and outcomes in patients with asymptomatic, mild, or moderate COVID-19 in home isolation who used AYUSH-64 for COVID-19.MethodsCross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Similarly, study result showed that 61% respondents responded that production and sharing of E-flier contained valuable information and SOPs regarding covid-19 for safety. Similarly, 21 has reported in his study that libraries have active role in Covid-19 pandemic by increasing public awareness regarding prevention and SOPs 22. 23, 24…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, study result showed that 61% respondents responded that production and sharing of E-flier contained valuable information and SOPs regarding covid-19 for safety. Similarly, 21 has reported in his study that libraries have active role in Covid-19 pandemic by increasing public awareness regarding prevention and SOPs 22. 23, 24…”
Section: Discussionmentioning
confidence: 83%
“…Ten "Yoga & Naturopathy" studies and the first Ayurvedic study looked at reducing"covid-19" -related psychological stress as well as its accompanying symptoms, which include sadness, anxiety, and sleeplessness. One out of ten "Yoga and Naturopathy" studies was found to be single-armed, while the other nine were either double-or single-blind [10]. Four randomized controlled trials compared "conventional care" (CC) with and without intervention.…”
Section: Mitigation Of Psychological Impact Of"covid-19"mentioning
confidence: 99%
“…Stress scale and serum cortisol level were both included as the outcome measure of one research. The sole Ayurvedic study regarding stress reduction used a double-blind design [10]. The Brahmi (Bacopa monnieri) group received therapy, whereas the control group received nothing.…”
Section: Mitigation Of Psychological Impact Of"covid-19"mentioning
confidence: 99%
“…AYUSH 64 hastened clinical recovery, reduced hospitalization period, and showed early persistent health benefits with minimal/absent drug-related side effects ( Chopra et al, 2023 ). Incidentally in the large community study, Ayush 64 found to provide good therapeutic care to patients with asymptomatic, mild, and moderate COVID-19 in home isolation too ( Srikanth et al, 2022 ). Meta-analysis suggested that add-on AYUSH-64 likely provides therapeutic benefits by reducing time to symptom resolution (mean difference [MD] 2.35 days lower [95% confidence interval, CI; 4.05 lower to 0.65 lower]) and hastening clinical improvement (365 more per 1000 [95% CI; 4 more to 1000 more]) in mild-to-moderate COVID-19 patients ( Thakar et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%